2018
DOI: 10.3390/nu11010055
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of New Technology-Based Tools for Dietary Intake Assessment—An ILSI Europe Dietary Intake and Exposure Task Force Evaluation

Abstract: Background: New technology-based dietary assessment tools, including Web-based programs, mobile applications, and wearable devices, may improve accuracy and reduce costs of dietary data collection and processing. The International Life Sciences Institute (ILSI) Europe Dietary Intake and Exposure Task Force launched this project to evaluate new tools in order to recommend general quality standards for future applications. Methods: A comprehensive literature search identified technology-based dietary assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
194
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(202 citation statements)
references
References 111 publications
5
194
1
2
Order By: Relevance
“…Furthermore, these studies were on infants and young children (up to age 4.5 years old), where dietary intake was completed by adult carers which may increase accuracy. A wide LOA was found for the Livingstone weighed food diary validated against the DLW (n = 58,38). This may be due to the the wide age range (7-18 years old) with older children more involved in recording intake, and/or because data for this study was obtained via different sources such as parents, child minders and school lunch supervisory staff some of whom may not have been trained adequately in completing the DAT [20].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, these studies were on infants and young children (up to age 4.5 years old), where dietary intake was completed by adult carers which may increase accuracy. A wide LOA was found for the Livingstone weighed food diary validated against the DLW (n = 58,38). This may be due to the the wide age range (7-18 years old) with older children more involved in recording intake, and/or because data for this study was obtained via different sources such as parents, child minders and school lunch supervisory staff some of whom may not have been trained adequately in completing the DAT [20].…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, such tools may assist children and adolescents with lower cognitive and literacy skills to report their food intake. However, challenges remain relating to following procedures associated with these DATs, food databases and portion size estimation [58]. In this review, two DATs were identified which made use of new technologies which were both on-line 24-h recalls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor literacy and education levels can compound a lack of clarity and attention to portion sizes and ingredients used, in turn affecting the accuracy of the dietary records [24,27,32,[51][52][53]. Despite the fact that most prospective studies begin with a degree of training for respondents, the effectiveness and receptiveness of the training is dependent on the participants' abilities to grasp and execute these concepts [24,32,51,52]. This is further amplified by the complexity of Southeast Asian diets, and the reliance on food consumed outside the home can make it difficult for individuals to be aware of all the ingredients in the food [32,44].…”
Section: Limitations Of Current Dietary Recording Methodsmentioning
confidence: 99%
“…Difference in the response of individuals to dietary components is well‐recognised and an interest in personalisation is a consequence of a better understanding of how diet affects health, the new wearable technologies (such as fitness trackers and mobile apps) that now enable better and continuous measurement of markers of individual health and fitness parameters, and new analytical tools that interpret this flow of data and transform it into user‐friendly practical information for individuals (Ordovas et al ; Eldridge et al ). There is no formal definition of personalised nutrition but it is described by Ordovas et al () as an approach that uses information on individual characteristics to develop targeted nutritional advice, products and services.…”
Section: Personalised Nutritionmentioning
confidence: 99%